Membedah Realitas Sosial Ekonomi Warung Latengan Melalui Kajian Integratif RRA dan SWOT - Nurina Adi Paramitha; Hendra Syahputra; Sari Dewi Poerwanti; Nurcahyaning Dwi Kusumaningrum; Sukron Makmun (Jurnal Intervensi Sosial, 2025)
MSMEs, especially micro-enterprises, act as a safety valve in addressing economic challenges. Although the existence of latengan stalls as micro-enterprises can absorb labor, this indicates that many workers come from the lower classes, the problem of unpaid family workers, and urban spatial planning issues. This study aims to dissect the socio-economic reality of latengan stalls through an integrative Rapid Rural Appraisal (RRA) and SWOT analysis. Through the RRA, data were obtained regarding latengan stall vendors with low human resources and limited capital, latengan stall operations involving unpaid family workers including children, and latengan stall cash flow problems. The Javanese trading ethos allows latengan stall vendors to utilize positive social capital for economic improvement, but this ethos also has a negative impact that causes stall cash flow to be unstable. Change strategies from the RRA and SWOT analysis include strategies to maximize the potential of the surrounding environment, participate in MSME training, utilize capital provided for MSMEs, create simple SOPs for stall operations, and maximize social capital for economic improvement.